2018
DOI: 10.5130/ajceb.v18i2.5872
|View full text |Cite
|
Sign up to set email alerts
|

Relational Contracting Conceptual Model for Public Sector Construction Organisations: An Indian Context

Abstract: Adoption of relational contracting in public sector construction organisations is more difficult than in private sector organisations due to the inherent rigidity of public sector. Therefore, implementation of the relational contracting processes should be treated as an organisational change management process in public sector organisations. The purpose of this paper is to develop a relational contracting conceptual model (RCMM) by integrating success factors for positive change management in public sector org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Tawalare and Laishram (2018) report that communication is essential for relational contracting success, and they define relational contracting as a partnership or alliance in India's public sector construction organisation. The importance of communication in a partnership setting has also been established in a study by Ee et al (2013a, 2013b), who investigate the impact of communication on business process outsourcing success in Malaysia’s banking industry.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Tawalare and Laishram (2018) report that communication is essential for relational contracting success, and they define relational contracting as a partnership or alliance in India's public sector construction organisation. The importance of communication in a partnership setting has also been established in a study by Ee et al (2013a, 2013b), who investigate the impact of communication on business process outsourcing success in Malaysia’s banking industry.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Trust, leadership and communication quality have been found to play an essential role in determining performance in teams as well as organisational and interorganisational relationships, including in the public–private partnership (PPP) setting (Mohr and Spekman, 1994; Jacobson and Choi, 2008; Ee et al , 2013a; Gesell, 2014; Robert and You, 2018; Tawalare and Laishram, 2018; Warsen et al , 2018, 2019; Tawalare et al , 2020). Effective leadership is vital in PPP settings because past studies have found that leadership directly impacts a project’s outcome (Hauschildt et al , 2000; Shenhar et al , 2002; Nixon et al , 2012; Laureani and Antony, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In order to highlight this concept, some researchers [7,15,21,22] have established a continuum of partnerships that outlines four main stages: competition, cooperation, collaboration, and coalescence. Moreover, "competition" describes the typical owner-contractor relationship, where every party pursues distinct objectives and "working together" is not emphasized.…”
Section: Partnering In Construction Projectsmentioning
confidence: 99%
“…Third, Project Alliance (PA) is widely employed in the Australian and Finnish public sector (Walker and Lloyd-Walker 2015) and involves a joint contract where all parties share risk in design and construction phases. Fourth, Project Partnering (PP) involves either a legally binding contract or a voluntary non-contractual agreement between partners (Hall et al 2018, Tawalare andLaishram 2018). PP consists of two or more parties who work together to achieve specific business objectives (Eriksson 2010).…”
Section: Characteristics Of Relational Contracting Strategiesmentioning
confidence: 99%